Communication and Exchange of Specialized Health-Related Support Among People With Experiential Similarity on Facebook. Issue 10 (3rd October 2017) - Gage-Bouchard, Elizabeth A.; LaValley, Susan; Mollica, Michelle; Beaupin, Lynda Kwon
ABSTRACT: Social support is an important factor that shapes how people cope with illness, and health-related communication among peers managing the same illness (network ties with experiential similarity) offers specialized information, resources, and emotional support. Facebook has become a ubiquitous part of many Americans' lives, and may offer a way for patients and caregivers experiencing a similar illness to exchange specialized health-related support. However, little is known about the content of communication among people who have coped with the same illness on personal Facebook pages. We conducted a content analysis of 12 months of data from 18 publicly available Facebook pages hosted by parents of children with acute lymphoblastic leukemia, focusing on communication between users who self-identified as parents of pediatric cancer patients. Support exchanges between users with experiential similarity contained highly specialized health-related information, including information about health services use, symptom recognition, compliance, medication use, treatment protocols, and medical procedures. Parents also exchanged tailored emotional support through comparison, empathy, encouragement, and hope. Building upon previous research documenting that social media use can widen and diversify support networks, our findings show that cancer caregivers access specialized health-related informational and emotional support through communication with others who have experienced the same illness on personal Facebook pages. These findings have implications for health communication practice and offer evidence to tailor M-Health interventions that leverage existing social media platforms to enhance peer support for patients and caregivers.